Analysis of improved pulse-shaped RPRCC for synchronous and asynchronous MC-CDMA system under multi-user CFO estimation techniques. (2016) - Chitra, S.; Kumaratharan, N.
Long-term evolution (LTE) is one of the emerging fourth-generation (4G) standards for high-speed wireless networks. Due to the high spectral efficiency, large system capacity and robustness to multi-path fading, multi-carrier code division multiple access (MC-CDMA) system is a highly apt standard for 4G. However, MC-CDMA systems are more susceptible to carrier frequency offset (CFO) due to the discrepancy between the carrier frequencies of transmitter and receiver local oscillators. CFO effects loss of orthogonality among the subcarriers and introduces intercarrier interference (ICI). To reduce ICI and to confine the interference only to a limited number of neighbouring subcarriers, an improved pulse shaping with receiver phase rotated conjugate cancellation (RPRCC) scheme is proposed in this paper. Simulation results are provided to validate the performance of the proposed method using different spreading codes such as Walsh-Hadamard code, m-sequence and gold code in both synchronous and asynchronous transmissions.